2009
DOI: 10.1088/0957-0233/20/12/124015
|View full text |Cite
|
Sign up to set email alerts
|

A quadruple wavelength IR sensor system for label-free tumour screening

Abstract: In this contribution, we present a novel quadruple wavelength infrared sensor system for measuring the CH2-symmetric/CH2-antisymmetric stretch ratio of biological cells. This ratio can be used as a marker to distinguish between healthy and carcinoma cells. Compared to common techniques our system does not require specific labelling or staining, or the use of expensive liquid nitrogen cooled IR spectrometers. Two of the four wavelengths, 3.33 and 3.57 µm, are used as reference points and the other two represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…[15][16][17] To distinguish normal from malignant cells we propose a sensing principle that is based on a four-wavelength mid-infrared absorbance measurement, to derive the CH 2 -symmetric/CH 2 -antisymmetric stretch ratio. 18 The monitoring of CH 2 -stretches of phospholipid acyl enables to look at changes in molecular interactions and it inherently compensates for differences in the cell amount and measurement spot size. Instead of measuring the frequency shifts of either the CH 2 -symmetric or CH 2 -antisymmetric stretch caused by trans/ gauche conformation changes of the acyl chain, 19 the cell type discrimination method depends on the ratio change between the two CH 2 -stretches.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] To distinguish normal from malignant cells we propose a sensing principle that is based on a four-wavelength mid-infrared absorbance measurement, to derive the CH 2 -symmetric/CH 2 -antisymmetric stretch ratio. 18 The monitoring of CH 2 -stretches of phospholipid acyl enables to look at changes in molecular interactions and it inherently compensates for differences in the cell amount and measurement spot size. Instead of measuring the frequency shifts of either the CH 2 -symmetric or CH 2 -antisymmetric stretch caused by trans/ gauche conformation changes of the acyl chain, 19 the cell type discrimination method depends on the ratio change between the two CH 2 -stretches.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, signal in infrared spectroscopy originates with the most intrinsic part of a sample—its molecular structure. Infrared measurements can thus be leveraged for automated tissue classification and cancer identification5678. Most significant is their ability to record the conformational changes of proteins that elucidate the molecular mechanisms of their function9101112.…”
mentioning
confidence: 99%
“…In the case of cancer, a reduction in the cholesterol concentration leads to a molecular disorder with a consequent increase of the CH 2 symmetric stretch vibration [48]. Our previous studies on melanoma cell lines showed an increase in the CH 2 stretch ratio when cholesterol is sequestered from the plasma membrane [43]. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, anomalies in the infrared absorption of methylene (CH 2 ) groups have been reported in the literature in the occurrence of cancer [41,42]. We realized an infrared quadruple sensor for the CH 2 stretch ratio determination of different melanoma cell lines [43,44]. Increased CH 2 stretch ratio values were observed for melanoma cells compared to the healthy reference.…”
Section: Introductionmentioning
confidence: 99%